Sandfly Fever Viruses Attenuate the Type I Interferon Response by Targeting the Phosphorylation of JAK-STAT Components - Moalem, Yarden; Malis, Yehonathan; Voloshin, Konstantin; Dukhovny, Anna; Hirschberg, Koret; Sklan, Ella H. (Frontiers in Immunology, 2022)
Sandfly fever viruses are emerging Phleboviruses typically causing mild febrile illness. Some strains, however, can cause severe and occasionally fatal neuro-invasive disease. Like most viruses, Phleboviruses have devised various strategies to inhibit the type I interferon (IFN) response to support a productive infection. Still, most of the strategies identified so far focus on inhibiting the sensing arm of the IFN response. In contrast, the effect of sandfly virus infection on signaling from the IFN receptor is less characterized. Therefore, we tested the effect of sandfly fever virus Naples (SFNV) and Sicily (SFSV) infection on IFN signaling. We found that infection with either of these viruses inhibits signaling from the IFN receptor by inhibiting STAT1 phosphorylation and nuclear localization. We show that the viral nonstructural protein NSs mediates these effects, but only NSs from SFNV was found to interact with STAT1 directly. Thus, we tested the upstream IFN signaling components and found that Janus kinase 1 (Jak1) phosphorylation is also impaired by infection. Furthermore, the NSs proteins from both viruses directly interacted with Jak1. Last, we show that IFN inhibition by SFNV and SFSV is most likely downstream of the IFN receptor at the Jak1 level. Overall, our results reveal the multiple strategies used by these related viruses to overcome host defenses.